Evaluation of results of total knee replacement by computer assisted navigation and conventional techniques - Rajat Saran (International Journal of Medical Research and Review, 2016)
Introduction: Accurate component implantation and eventually the overall limb alignment are the essential requirements of a successful knee arthroplasty. Computer assisted navigation came into vogue with a claim of precision in aligning the limb as compared with the conventional jig based technique. This retrospective study evaluates the results of fifteen cases of total knee arthroplasty performed by the conventional technique and five cases, by the computer assisted navigation.Methods: This retrospective study was carried out at Ayushman hospital and Chirayu medical college, Bhopal from1993 to 2014. All patients selected, were suffering from tri -compartmental osteoarthritis of the knees having severe pain and varus deformity, except one who had post traumatic secondary osteoarthritis.. In fifteen cases total knee arthroplasty was done by using the jig based conventional technique whereas computer assisted navigation was used in five cases.Results: Intraoperatively less blood loss and a comparatively comfortable immediate post operative period were observed. However there was no appreciable advantage noticed in the long term results.Conclusion: Computer navigation by virtue of its feedback on screen during the surgery helped, to improve the accuracy of aligning the mechanical axis, whereas in the conventional jig based surgery, dependence was entirely on visual perception of the angles and cuts.